SOME INITIAL COMMENTS ABOUT ANCIENT COINS FOUND IN PANGTIENG VILLAGE (LAT COMMUNE, LACDUONG DISTRICT, LAMDONG PROVINCE) - Cao Thế Trình; Nguyễn Huy Khuyến; Mai Minh Nhật (Tạp chí Khoa học Đại học Đà Lạt)
In recent years, Pangtieng villagers (Lat commune, Lacduong district, Lamdong province) have found quintals of ancient coins. Only a small amount of them remains while the rest was lost (because of scrapselling). With 416 remained ancient coins, the authors have verified 42 ancient coin names, including a number of Vietnamese names (An Phap Nguyen Bao, Canh Hung Thong Bao...), and many those of Chinese currency (coin names in the age of the Tang, Northern Song, Ming and Qing dinasties). It is possible that the coins found are stolen by Champa aristocracy in the attacks on the palace of Nguyen Lords in Thuan Thanh in the end of eighteenth century. In order to avoid the arrest of Nguyen Lords, the Chams resided temporarily in Pang Tieng. Later, the Chams buried the money in Pang Tieng before taking refuge in Cambodia.